Authorship and Citations in Foot and Ankle International from 1980-2017. Issue 3 (14th September 2018) - Bohl, Daniel; Wakefield, Connor; He, Emily; Movassaghi, Kamran; Holmes, George; Lin, Johnny; Hamid, Kamran; Lee, Simon
Category: Other Introduction/Purpose: Orthopaedic foot and ankle surgery is a young and rapidly evolving orthopaedic subspecialty. Little is known regarding the authors contributing to the field. The purpose of this study is to characterize the demographics of the authors publishing foot and ankle research since the inception of the research journal of the American Orthopaedic Foot and Ankle Society. Methods: All publications in the journal Foot and Ankle International between 1980 and 2017 were reviewed. Papers were characterized in terms of number of authors, number of institutions, and number of references. The first and corresponding authors were also characterized in terms of country of origin, gender, and degree qualification. Each of these characteristics was tested for trends over time. Results: In total, 5, 323 publications were reviewed, including 4, 297 research articles, 367 case reports, 262 editorials, 159 letters, and 121 technique tips. The mean number of authors per paper increased from 2.3 during the 1980s to 4.3 during the 2010s (p<0.001). The percent of publications with female first authors increased from 4.9% during the 1980s to 13.2% during the 2010s (p<0.001). The country of origin shifted markedly away from the United States during the 1980s towards Europe and other countries during the 2010s (Figure 1). Podiatrists consisted of 1.3% of first authors and 1.4% of corresponding authors—these proportions did not meaningfully change over time (p>0.05). The mean number of references to other work increased from 13.8 during the 1980s to 24.4 during the 2010s (p<0.001). Conclusion: The authors of the foot and ankle literature have changed markedly over the past 4 decades. Most notably, there have been shifts towards female and international authorship. The number of authors per paper has also nearly doubled over time. Such trends are likely to continue as the field of foot and ankle grows.